Green, brown, and probability & brownian motion on the line - Chung, Kai Lai (World Scientific, 2002)
Emphasizes the methodology of Brownian motion in the relatively simple case of one-dimensional space. Numerous exercises are included. For graduate students and researchers in probability and statistics. Softcover. Hardcover available